Pelatihan Perancangan Website Profil Kelurahan Bontonompo - Aris, Valentino; Alam, Syamsu; Ashdaq, Muhammad; Taufik, Muhammad; Muh. Jamil (Yayasan Literasi Sains Indonesia, 2023)
The background for this service activity is that the website usage level in the sub-district in providing information and services quickly and in real-time still needs to be higher. Therefore, efforts are required to provide education and technical skills for designing a village website. This activity will be carried out in Bontonompo Village, Gowa Regency on may 18, 2023. This Community Partnership Program activity is carried out as a Bontonompo Village Profile Website Design Training, providing online media for communication, information, and services, especially for the urban village community and the general public visiting the Bontonompo Village. This training activity used the lecture and demonstration method, which lasted for one day with twenty participants who were representatives from all Bontonompo Sub-district Offices, Gowa Regency. The output of this training activity is the official website design for the Bontonompo Village, Gowa Regency. This design includes our home, profile, news, and contact pages. Apart from that, the follow-up program of this activity was also discussed between the Bontonompo Village and the Service Team in the form of Designing the Official Website for the Bontonompo Village and a Website-based Online Service Database.